2023
DOI: 10.2471/blt.22.288797
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-based antimicrobial stewardship, India

Abstract: Objective To establish a framework for implementing antimicrobial stewardship in Indian tertiary care hospitals, and identify challenges and enablers for implementation. Methods Over 2018–2021 the Indian Council of Medical Research followed a systematic approach to establish a framework for implementation of antimicrobial stewardship in Indian hospitals. We selected 20 Indian tertiary care hospitals to study the feasibility of implementing a stewardship programme. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, this study excluded all patients taking oral vancomycin thus making the calculation of unsuitable vancomycin usage a likely misestimation; though it is uncertain whether the result is an under- or overestimation. Despite this, India does not currently have a national-level antimicrobial stewardship plan [ 44 ]. Antimicrobial stewardship programs have demonstrated the ability to lower both antibiotic consumption and resistance; consequently, this has become a key strategy used to tackle AMR elsewhere [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study excluded all patients taking oral vancomycin thus making the calculation of unsuitable vancomycin usage a likely misestimation; though it is uncertain whether the result is an under- or overestimation. Despite this, India does not currently have a national-level antimicrobial stewardship plan [ 44 ]. Antimicrobial stewardship programs have demonstrated the ability to lower both antibiotic consumption and resistance; consequently, this has become a key strategy used to tackle AMR elsewhere [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial stewardship interventions, which were introduced in 2019 in India (Walia et al., 2019 ), were used to monitor the progress and implementation of the stewardship program in India between 2019 and 2021. The results indicated that the majority of tertiary hospitals implemented antimicrobial stewardship programs in their hospitals with the help of funding and capacity‐building activities from the Indian Council of Medical Research (Vijay et al., 2023 ). Another study used this policy document (Walia et al., 2019 ) to identify antibiotic prescription patterns after the decline of a major COVID‐19 wave at a dedicated COVID‐19 hospital in India.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies evaluating the impact of the pandemic on UTI and antimicrobial resistance [9][10][11]. With increased awareness about antimicrobial stewardship, most hospitals are shifting to the rational use of antibiotics and updating their antibiogram periodically [12]. But, in community settings, there is still a long way to go [13].…”
Section: Discussionmentioning
confidence: 99%